Molecular diagnostics of gliomas: state of the art - Riemenschneider, Markus J. (Springer-Verlag, 2010)
Modern neuropathology serves a key function in the multidisciplinary management of brain tumor patients. Owing to the recent advancements in molecular neurooncology, the neuropathological assessment of brain tumors is no longer restricted to provide information on a tumor’s histological type and malignancy grade, but may be complemented by a growing number of molecular tests for clinically relevant tissue-based biomarkers. This article provides an overview and critical appraisal of the types of genetic and epigenetic aberrations that have gained significance in the molecular diagnostics of gliomas, namely deletions of chromosome arms 1p and 19q, promoter hypermethylation of the O6-methylguanine-methyl-transferase (MGMT) gene, and the mutation status of the IDH1 and IDH2 genes. In addition, the frequent oncogenic aberration of BRAF in pilocytic astrocytomas may serve as a novel diagnostic marker and therapeutic target. Finally, this review will summarize recent mechanistic insights into the molecular alterations underlying treatment resistance in malignant gliomas and outline the potential of genome-wide profiling approaches for increasing our repertoire of clinically useful glioma markers.